(3TQM GdeYGQa GdZjHjI Ydi GdbUjOI GdYjfjIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s; (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj, bWH GdOjf,J (B832 (3g` s ((3GdHUQI s)
(3ChdgG (B:s
(3gPG TQM dWja hVYJg HGdYLd Ydi bUjOI HMQ GdMbGFb GdEdGgjI GdTjN YHOGdcQje GdLjdj s
(3BNQgG (B:s
(3eG jage GdSQEdG cd QHGfj YGTb agje ef Hj eZQe YGfj GfJgi s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
Keywords: (3GdJUha hGdBOGH GdTQYjIs